Prediksi Permintaan Produksi dan Strategi Pemasaran UMKM Pia Aldista Menggunakan Analisis Markov dan SWOT - Alis Suleman; Ismail Djakaria; La Ode Nashar (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
MSMEs play a vital role in national economic growth, but fluctuations in production demand pose a challenge in maintaining operational stability. The study on the Pia Lumer Aldista MSME aims to predict production demand and formulate marketing strategies through Markov Chain Analysis and SWOT. Markov Chain is used to model demand transition patterns based on the last three years of data and determine steady-state conditions, while SWOT identifies internal and external factors that influence marketing strategies. The Chi-Square Test results indicate that the data meets the Markov assumptions. Furthermore, the analysis results indicate that the original chocolate variant will stabilize in the 10th period with a decrease of 38.4%, while pandan chocolate is stable in the first period but experiences a drastic decrease of 29.4%. The SWOT analysis produces an IFAS score of 3.195 and an EFAS score of 3.148, placing the MSME in Quadrant I. Therefore, aggressive strategies are recommended, such as strengthening product uniqueness, lowering prices, expanding markets, and optimizing distribution. The approach of these two methods helps anticipate market changes and increase business competitiveness.